The chow maniac - Chien, Vivien (Chien, Vivien. Noodle shop mystery, 2025)
When Lydia brings Lana onto the case, three of the members of an elite Asian order known as the Eight Immortals have already been murdered. Each member of the order holds one item that represents their immortal counterpart, and someone is dying to get their hands on them all. Lydia's client insists he -- and only he -- knows who will be next and wants the murderer captured before there is another victim. Riding below the line of three cities of law enforcement and Lana's own boyfriend, Detective Adam Trudeau, the two women must tread lightly as they infiltrate a secret organization that even the Mahjong Matrons know nothing about. And somehow protect the next victim without letting on that she's in danger. As they dig deeper into the case, Lana finds there are unexpected associations within Asia Village and potential ties to her own family that could be devastating. With the stakes raised on the toughest case she's ever worked, will Lana be able to keep her own emotions out of the investigation? And will the murderer be found before they become the ultimate "immortal"? -- Provided by publisher.